Linear quadratic gaussian (LQG) controller for inverted pendulum - Ahmad, Norhidayah (2013)
The inverted pendulum is a classical control problem in dynamics and control theory which is the system encounter highly nonlinear and unstable system. Basically, the design of an inverted pendulum system consist of a cart or carriage which it can move horizontally along its track, where there is dc motor embedded in the cart to drive it, while on the cart, there is pendulum that mounted on it. For visualization purpose, the inverted pendulum system had similar concept when trying to balance a broomstick with hand. Since inverted pendulum is unstable system, the controller was introduced. Linear Quadratic Gaussian (LQG) is combination of multivariate function such as Linear Quadratic Regulator (LQR) and Kalman Filter. Linear Quadratic Gaussian (LQG) is developed as an optimal and effective controller that will be used to place cart at desired position and at the same time to make sure the pendulum is always erected in its inverted position during movement of cart. The simulation study was stimulated by using MATLAB and Simulink software. As conclusion, through simulation the inverted pendulum can be stabilized by the LQG controller.